Financing job guarantee schemes by oil revenue: the case of Iran - Zahra Karimi (Levy Economics Institute of Bard College, 2008)
Iran's constitution emphasizes social justice and obliges government to provide a job for every citizen. But in fact, the government's duty to provide jobs has shifted to government support for a measure designed to create new employment opportunities through subsidized loans to the private sector. This policy has not been successful to date, and the current stock of unemployed workers is about three million12.75 percent of the country's labor force. To realize the desire of the Iranian people to achieve full employment and social justice, the government must implement employment guarantee schemes, or EGS, in the most deprived areas. Elected town and village councils can design and manage the public works with the help of other government, as well as nongovernment, institutions. Programs can be financed using less than 10 percent of the annual oil-exporting revenue that is deposited in the Oil Stabilization Fund.
Keywords: E51; E63; J01; J08; 330; Job Guarantee; Full Employment; Iran; Employment Policies